1148 A Comparison of Two Strategies for the Management of Patent Ductus Arteriosus (PDA). (October 2012) - Paweletz, A; Woodger, K; Gardiner, D; Subhedar, N
Abstract : Background and Aims: The management of PDA in extremely preterm infants is controversial and there is no agreed optimal approach. Strategies that are commonly used include prophylactic, early asymptomatic or late symptomatic therapy. We describe our experience in changing from prophylactic indomethacin to late symptomatic treatment with ibuprofen. Methods: We collected data on all babies admitted < 28 weeks' gestation and/or < 1000g from an electronic patient database. We compared PDA diagnosis management, demographics and clinical outcomes in two six month time periods: period 1 was when we used a prophylaxis strategy with indomethacin and period 2 when we changed to late symptomatic treatment with ibuprofen. Results: Conclusions: Changing from a strategy of indomethacin prophylaxis to selective, late symptomatic treatment of PDA with ibuprofen did not result in a significant increase in babies with severe IVH, chronic lung diasease or those needing duct ligation.